Interest and Enthusiasm in Learning English as a foreign Language in a Senior High School in Bangka Belitung Islands, Indonesia and How Both Relate to English Achievement - Hukama Rizky Yusriyah; Eryansyah Eryansyah; Dedi Kurniawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Interest and enthusiasm are internal factors known to an extent to have an influence toward learning in general. This study aims at checking these three variables relationship: interest, enthusiasm, and English achievement.  It was conducted in Sungai Liat Regency, Bangka Belitung Islands, Indonesia, in a state senior high school which provided 70 students to be the sample of this study from the population of 183 students in the school. The instruments used were: Interest and Enthusiasm Questionnaire and Students’ English score documentation. The data collected using the questionnaire were divided into two parts: interest and enthusiasm. Both data were analyzed using Pearson Product Moment Correlation Coefficient to see the association of interest toward enthusiasm. Furthermore, data from each one of the two variables and combined data from both variables were also analyzed using Pearson Product Moment Correlation Coefficient to find out how both variables as relate toward English achievement. The results show that interest in learning English had a strong significant association toward enthusiasm (r(70)=.77, p=0.00).  Furthermore, both interest and enthusiasm had a significant association toward English achievement (respectively: r(70)=.40, p=0.001; r(70)=.24, p=0.046).  Moreover, the combination of both interest and enthusiasm also showed a strong association toward English achievement (r(70)=.343, p=0.004). This study also provided some implications and recommendations for further research.